Peningkatan Kompetensi Profesional Guru Melalui Diseminasi Metode Perawatan Dan Perbaikan Engine Management System (EMS) Pada Mobil Keluaran Terbaru Di SMKN 1 Tuban - Amat Nyoto; Erwin Komara Mindarta; Prihatono; Hadi Wibowo; Anda Permadani (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The professionalism of vocational school teachers is also seen as lacking. This is shown by the high number of vocational school teachers who do not yet have teaching certificates or skill competency certificates. Educator certification is an indicator that the teacher has been declared to have met the requirements and passed the competency test to become a professional teacher. On the other hand, a skills competency certificate is an indicator that a vocational teacher is an expert in a vocational field. The problem is that not all teachers have the opportunity to take part in programs/disseminations either officially organized by the government or private sector to improve professional competence. The community service implementation team from the UM Automotive Engineering Education Undergraduate study program provides training specifically for automotive engineering teachers at the vocational school with the aim of transferring the latest knowledge related to automotive advanced, namely EMS, to improve teachers' professional competence. Training methods include site surveys, formulating training materials, making schedules, preparing tools, materials and training instructors up to evaluation. EMS training was held offline in accordance with health protocols, and the results were an increase in teacher professional competence as evidenced by the mean posttest score (70.29) > mean pretest score (62.11) and the difference was real Sig. (2-tailed) of 0.000 at 0.05. Apart from that, from the resource person's explanation, teachers know how to teach EMS to students.